MENINGKATKAN KUALITAS PENDIDIKAN DI PERGURUAN TINGGI: ANALISIS STRATEGI KEPEMIMPINAN YANG EFEKTIF - Beatus Tambaip; Alexander Phuk Tjilen (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2023)
The purpose of this study is to provide an overview of the strategies used by leaders in tertiary institutions, especially at the faculty level, in improving the quality of education. This research is a survey conducted to identify the views of each respondent in assessing the quality of education in tertiary institutions by looking at the strategies used by the leaders of the Respondents in this study, namely the academic community at the Faculty of Social and Political Sciences, Musamus University. The measuring tool designed in the form of a questionnaire related to the seven categories in Malcolm Baldrige. The questionnaire created was an adaptation of the original MBCfPE Education Criteria application. Questions that were originally in the form of essays were changed to form of choice answers to make it easier for respondents to answer and direct them to the basic needs of each category. The results of the study show that the strategies used by leaders in improving the quality of education are carried out by establishing a clear vision and mission, building a solid team, and implementing an appropriate performance measurement system. Effective leadership in tertiary institutions must have a clear vision and mission to motivate staff and students, and direct universities to achieve long-term strategic goals.